Sympatric ecological divergence associated with a color polymorphism - Kusche, Henrik; Elmer, Kathryn R.; Meyer, Axel (My University, 2015)
Background
Color polymorphisms are a conspicuous feature of many species and a way to address broad ecological and evolutionary questions. Three potential major evolutionary fates of color polymorphisms are conceivable over time: maintenance, loss, or speciation. However, the understanding of color polymorphisms and their evolutionary implications is frequently impaired by sex-linkage of coloration, unknown inheritance patterns, difficulties in phenotypic characterization, and a lack of evolutionary replicates. Hence, the role of color polymorphisms in promoting ecological and evolutionary diversification remains poorly understood. In this context, we assessed the ecological and evolutionary consequences of a color polymorphic study system that is not hampered by these restrictions: the repeated adaptive radiations of the gold/dark Midas cichlid fishes (the Amphilophus citrinellus species complex) from the great lakes and crater lakes of Nicaragua, Central America.
Results
We conducted multi-trait morphological and ecological analyses from ten populations of this young adaptive radiation (<6,000 years old), which revealed sympatric ecological differentiation associated with the conspicuous binary (gold/dark) color polymorphism. Varying degrees of intraspecific ecological divergence were observed across the ten color morph pairs, but most pairs exhibited a consistently parallel ecological and evolutionary trajectory across populations. Specifically, gold Midas cichlids are frequently deeper-bodied, have more robust pharyngeal jaws, and feed at a lower trophic level compared to conspecific, sympatric dark individuals. A common garden experiment suggests there is a genetic correlation of color and eco-morphological traits.
Conclusions
We demonstrate unprecedented ecological and evolutionary consequences of color polymorphism in this adaptive radiation. Across the species complex, sympatric conspecific individuals differed in eco-morphology depending on color morph (gold/dark) and the axis of differentiation tended to be consistent across replicates. The consistent divergence across wild populations and the common garden experiment suggests that color is genetically correlated to ecology. Because Midas cichlids are known to mate color assortatively, the putative genetic correlation of this color polymorphism with an eco-morphological divergence suggests an innate potential to promote ecological and evolutionary divergence across this species complex. However, there are to date no examples of speciation based on color in this radiation, suggesting long-term maintenance of this color polymorphism.
Keywords: Adaptive radiation, Ecological diversification, Evolutionary ecology, Parallel evolution, Color polymorphism, Stable isotope analysis, Crater lake, Cichlids, Genetic correlation, Pleiotropy, Genetic linkage; 570